2020
DOI: 10.3389/fcimb.2020.00436
|View full text |Cite
|
Sign up to set email alerts
|

CD103 Promotes the Pro-inflammatory Response of Gastric Resident CD4+ T Cell in Helicobacter pylori-Positive Gastritis

Abstract: CD103 is considered as a surface marker for the resident immune cells. However, little is known about the intrinsic function of CD103 in infection and inflammation. In this study, we found that CD103 was highly expressed in CD4 + T cells of the gastric mucosa from patients with H. pylori-positive gastritis. Mucosal resident CD103 + CD4 + T cells exhibited an increase in the CD45RO + CCR7 − effector memory phenotype and high expression of the chemokine receptors CXCR3 and CCR9 compared with those in CD103 − CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…All of the 51 patients were diagnosed as H. pylori -positive gastritis with pathological changes of mucosa, whereas 35 healthy controls are with H. pylori -negative results and normal mucosa (See Table 1 ). Gastritis was diagnosed when the depth of damaged mucosal tissue was <5 mm, while the depth of damaged tissue was >5 mm in gastric ulcer patients ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the 51 patients were diagnosed as H. pylori -positive gastritis with pathological changes of mucosa, whereas 35 healthy controls are with H. pylori -negative results and normal mucosa (See Table 1 ). Gastritis was diagnosed when the depth of damaged mucosal tissue was <5 mm, while the depth of damaged tissue was >5 mm in gastric ulcer patients ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gastritis induced by H. pylori infection is characterized by excessive mucosal inflammation, which is represented by the hypersecretion of mucus and cytokines, and inflammatory cell infiltration ( 20 , 21 ). Gastritis may lead to gastric perforation, gastrorrhagia, ulcers, and even worse, stomach cancer after further development ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…The procedure of cell staining and flow cytometry was previously described ( 5 ). For intracellular staining of IL-21, gastric CD4 + T cells were restimulated with 1 μg/ml anti-CD3 Ab (Clone UCHT1, BD), 1 μg/ml anti-CD28 Ab (Clone CD28.2, BD), and 3 μg/ml brefeldinA (eBioscience, CA, USA) for 12 h. The intracellular fixation/permeabilization buffer set (eBioscience, CA, USA) was used in IL-21 staining.…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that Th9-like MAIT cells are enriched in gastric tissue and revealed the positive correlation of Th9-producing MAIT cells with disease progression ( 4 ). We also reported that H. pylori -associated antigens induced the Th1 and Th17 response of gastric CD4 + T cells ( 5 ). These observations indicate the tight interactions between H. pylori and the different subsets of immune cells and elements in the mucosal tissue, which may contribute to inflammatory response and mucosal pathology.…”
Section: Introductionmentioning
confidence: 92%
“…aEb7-expressing cells are able to interact with epithelial (E-) cadherin expressed by intestinal epithelial cells (IECs) and may thereby be retained in the tissue (113). Furthermore, evidence from cancer and gastritis research suggests that this interaction serves as a costimulatory factor for T cell receptor activation in CD8 + and CD4 + T cells, respectively (114)(115)(116)(117). Despite CD103 expression being associated with a Treg phenotype in mice (118)(119)(120), recent evidence suggests a pro-inflammatory Th1, Th17 and Th1/17 phenotype for aEb7 + CD4 + T cells with reduced expression of Treg markers in the large intestine of UC patients, proposing a role for these cells in disease pathobiology (121).…”
Section: Integrin Blockade Beyond α4β7-blockade -Interfering With Retentionmentioning
confidence: 99%